HUBUNGAN PEMBERIAN MASSAGE COUNTERPRESSURE TERHADAP PENURUNAN INTENSITAS NYERI KALA I FASE AKTIF PADA IBU BERSALIN - Enggal Sari Maduratna; Selvia Nurul Qomari; Nailufar Firdaus (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Labor pain is a physiological process with different intensity for individuals with inconvenient disorders which result in feelings of fear and worry. The previous research showed that of 10, 7 mothers in labor said severe pain and even cried during contraction. The objective of research was to analyze differences in pain intensity in stage 1 active phase for delivering mothers given and not given counterpressure.This research employed quasy experimental design, that is, Static Group Comparison Design. Independent variable was counterpressure, and dependent variable was pain intensity in stage 1 active phase for delivering mothers. Population consisted of estimated mothers in labor in April – Mei 2020. Sample which used accidental sampling technique consisted 24 respondents. Research instrument used numeric pain scales and data analysis used Paired T Test and Independent Sample T-Test.Statistic result showed that ,with treatment, using Paired T Test, ρ (0,000) < α (0,05) meant Ha was accepted and without treatment ρ (0,005) < α (0,05) meant Ha was accepted. Independent Sample TTest showed that ρ-value (0,000) < α = 0,05 meant there was difference between those given counterpressure and not given counterpressure. Mothers in labor should not feel worried so that they cannot undergo increasing pains and can control pains with counterpressure.